A renewable energy-driven water treatment system in regional Western Australia - Shahnia, Farhad; Fornarelli, R.; Anda, M.; Bahri, P. (IEEE, 2018)
© 2017 IEEE. This paper presents a feasibility analysis for running a water treatment system by renewable energies in a regional town of Western Australia. The main motivation is the inadequate capacity in the electricity feeder supplying the town especially in summer. Instead of augmenting the feeder to the town to supply the electricity demand of the water treatment system, locally installed renewable energies seem to be sustainable, cost effective and attractive for the local electricity utility. This paper finds an economically attractive and technically feasible solution in the form of integrating a distributed system of rooftop solar photovoltaic systems with wind energy and existing grid to supply the energy demand of the town, as well as the new water treatment system. The proposed hybrid energy system provides electricity at a lower cost than the current energy solution, while improving the penetration of renewable energies in the region.